Framework for the adoption of e‐commerce: A case of South African retail grocery sector. Issue 5 (21st May 2019) - Johnson, Olufemi; Iyamu, Tiko
Abstract: Over the years, the adoption and use of e‐commerce have expanded widely in different organisations across the world, influenced by its potential benefits. Conversely, in spite of the benefits that have been commonly and widely reported, there are minimal adoption and use of e‐commerce by South African businesses, specifically, in the retail sector. The causes to the limited adoption of e‐commerce in South Africa are not known. This empirical study therefore investigates the factors that influence and affect the adoption and use of e‐commerce in the mainstream retail grocery sector in South Africa. A retail organisation was selected and used as a case in the study. Actor‐network theory (ANT) was employed as a lens to guide the analysis of the qualitative data. Based on empirical evidence, the findings, which include business drivers, stock of knowledge, alliance of actors, training and skills, and assimilation of processes, were found important in the adoption and use of e‐commerce. The factors are intended to guide how adoption and use of e‐commerce are conducted in the mainstream retail grocery sector in South Africa.